2014
DOI: 10.1002/pchj.55
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy: Public knowledge and beliefs about mental disorders in mainland China

Abstract: This study was concerned with the general mental health literacy of lay people in mainland China. It replicates in part many studies done in America, Australia, and Europe. A total of 212 participants were asked to read vignettes depicting people with schizophrenia, obsessive-compulsive disorder, social phobia, depression, bipolar disorder, stress, child attention-deficit hyperactivity disorder (ADHD), child depression, and child "daily troubles." For each vignette they were asked to label the vignette charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 73 publications
5
28
0
1
Order By: Relevance
“…Secondly, the analysis of social media posts can be helpful to identify the level of suicide literacy. Results (Table ) showed that poor knowledge of signs and treatments of suicide was evident, a finding that is consistent with other research on mental health literacy of Chinese people (Gong & Furnham, ; Rong et al, ; Wong & He, ). A total of 11.67% of posts conveyed incorrect knowledge regarding signs and treatments of suicide.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, the analysis of social media posts can be helpful to identify the level of suicide literacy. Results (Table ) showed that poor knowledge of signs and treatments of suicide was evident, a finding that is consistent with other research on mental health literacy of Chinese people (Gong & Furnham, ; Rong et al, ; Wong & He, ). A total of 11.67% of posts conveyed incorrect knowledge regarding signs and treatments of suicide.…”
Section: Discussionsupporting
confidence: 89%
“…The fictitious person described in the vignette was described as being too preoccupied with being clean, thus this may cause confusion with the correct OCD label. Similar mislabelling can also be found in Gong and Furnham (2014) and Loo et al's (2012) studies in which many participants also used the term "mysophobia" or in Chinese "潔癖" to refer to the symptoms described in the vignette. From these two studies, one may imply that the term "mysophobia" may 13 be used colloquially to refer to people that are fixated with cleanliness.…”
Section: Discussionmentioning
confidence: 93%
“…The mental disorders in the vignettes included post-traumatic stress disorder (PTSD), depression, obsessive-compulsive disorder (OCD), dependent personality disorder (DPD), schizotypal personality disorder (SPD), generalized anxiety disorder (GAD), agoraphobia, bipolar disorder, social phobia, panic disorder, narcissistic personality disorder (NPD), schizophrenia and antisocial personality disorder (APD) in which all of the vignettes were adapted from previous studies (Jorm, Christensen & Griffiths, 2005;Jorm, Wright & Morgan, 2007;Furnham & Anthony, 2010;Gong & Furnham, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies found that 23% to 60% of suicide attempters had psychiatric disorders (Gunnell & Frankel, ; Ikunaga, Nath, & Skinner, ). This inconsistency might be due to a poor mental health literacy among Chinese people (Gong & Furnham, ; Rong et al, ; Wong & He, ), which leads to an underestimation of the prevalence of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%